Penerapan PjBL pada Pembelajaran Berdiferensiasi Untuk Meningkatkan Keaktifan dan Hasil Belajar Kelas X SMA Materi Transpor Membran Sel - SURYANI, AGUSTINA ADHI; Maria Ulfah; E Murniati (Pascasarjana Universitas PGRI Semarang, 2024)
This is a Collaborative Classroom Action Research aimed at improving students' engagement and cognitive learning outcomes through the implementation of the Project Based Learning model in differentiated teaching on the topic of cell membrane transport systems. This research was conducted at State High School 8 Semarang in the first semester of the 2023/2024 academic year, with a research subject of 36 students in class XI-1. The research was conducted in two cycles. The instruments used included an observation sheet for student engagement and pretest-posttest questions. The results indicated that the level of successful student engagement in the first cycle was 44%, and it increased to 75% in the second cycle. The average student engagement percentage in the first cycle was 54%, which increased to 84% in the second cycle, with the average engagement outcomes in the observed aspects reaching 85%, classified as high. Furthermore, the improvement in student learning outcomes was 50% in the first cycle, increasing to 58% in the second cycle. In conclusion, the application of the Project Based Learning model proved effective in enhancing the engagement and learning outcomes of class XI-1 students at State High School 8 Semarang in the topic of cell membrane transport.